Peran Orang Tua terhadap Keterampilan Membaca Permulaan Siswa Kelas II SDN Lerep 04 Ungaran Barat Kabupaten Semarang - Puput Lestari; Atrianing Yessi Wijayanti; Nimas Puspitasari (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
Beginning reading is a fundamental skill that must be mastered by elementary school students, particularly in the early grades, as it serves as the foundation for further learning. Students with low beginning reading ability may experience difficulties in understanding instructional materials and achieving academic success. This study aimed to describe the role of parents in supporting the beginning reading skills of second-grade students at SDN Lerep 04, West Ungaran, Semarang Regency. This study employed a qualitative descriptive design involving one second-grade teacher, six parents, and six second-grade students. Data were collected through interviews and documentation and were validated using source triangulation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that parents played important roles as educators, facilitators, companions, and motivators. They supported children by introducing letters, guiding them in reading syllables and simple words, providing learning materials and facilities, accompanying them during reading activities at home, and encouraging them through praise, advice, and rewards. However, several obstacles were identified, including gadget use, limited parental time, children’s changing moods, and the influence of the play environment. The study concludes that the optimization of parental roles significantly contributes to the development of children’s beginning reading skills. Therefore, strong collaboration between schools and families is essential to foster literacy from an early age.Keywords: parental role, beginning reading, reading skills, elementary school students